2012
DOI: 10.1007/s00264-012-1482-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of orthopaedic surgeons in managing patients with fragility fracture

Abstract: Purpose Fragility fractures represent a major health problem, as they cause deformity, disability and increased mortality rates. Orthopaedic surgeons should identify patients with fragility fractures and manage their osteoporosis in order to reduce the risk of future fracture; therefore, orthopaedic surgeons' knowledge about managing fragile fracture should be evaluated. Methods A questionnaire was administered to 2,910 orthopaedic surgeons to address the respondents' knowledge. The questions covered the topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Vitamin D deficiency in the adult patient need not always be associated with frank radiological signs of osteomalacia. Other signs and symptoms like vague bone pains and proximal muscle weakness are not always evaluated or treated and hence patients may be labelled as clinically normal 23 , 24 . Even if patients in this group were clinically asymptomatic, they may all benefit from supplementation post injury considering the benefit of Vitamin D on bone health, calcium metabolism and improved rehabilitative potential 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency in the adult patient need not always be associated with frank radiological signs of osteomalacia. Other signs and symptoms like vague bone pains and proximal muscle weakness are not always evaluated or treated and hence patients may be labelled as clinically normal 23 , 24 . Even if patients in this group were clinically asymptomatic, they may all benefit from supplementation post injury considering the benefit of Vitamin D on bone health, calcium metabolism and improved rehabilitative potential 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and lifetime risk of any fracture doubles every decade after 50 year-old. 4 , 11 , 13 15 During the visit, a standard medical history also should be obtained, with particular attention paid to age, weight, personal and family history of fracture, physical inactivity, medication, alcohol, tobacco, and frailty.…”
Section: Scenariomentioning
confidence: 99%
“…Orthopedic residency and curricula may not provide sufficient knowledge or training to allow osteoporosis management. 11 Edwards et al 12 demonstrated a modest increase in certain aspects of bone health order pathways and treatment by using an electronic medical record order set. That intervention created with providers’ input increased the follow-up and treatment of patients with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…These research questions seem very important, because many orthopedic surgeons hesitate to screen patients with fragility fracture for osteoporosis, as they claim to be without knowledge about treating osteoporosis. In a survey of 2021 orthopedic surgeons, less than 10% answered that they would use BMD when evaluating patients with fragility fractures and only 17% claimed to have knowledge about managing osteoporosis according to the results of BMD analysis [2].…”
Section: Introductionmentioning
confidence: 99%